2002
DOI: 10.1128/mcb.22.6.1868-1880.2002
|View full text |Cite
|
Sign up to set email alerts
|

Control of DNA Replication and Chromosome Ploidy by Geminin and Cyclin A

Abstract: Alteration of the control of DNA replication and mitosis is considered to be a major cause of genome instability. To investigate the mechanism that controls DNA replication and genome stability, we used the RNA silencing-interference technique (RNAi) to eliminate the Drosophila geminin homologue from Schneider D2 (SD2) cells. Silencing of geminin by RNAi in SD2 cells leads to the cessation of mitosis and asynchronous overreplication of the genome, with cells containing single giant nuclei and partial ploidy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
201
2
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(244 citation statements)
references
References 52 publications
30
201
2
11
Order By: Relevance
“…This fits well with a crucial role of cyclin B/CDK1 complexes in this phenotype, probably together with cyclin A/CDK1 complexes. Indeed, re-replication has been reported after cyclin A ablation in drosophila, and also after cyclin A knock down together with Emi-1 in mammals (Mihaylov et al, 2002;Machida and Dutta, 2007). As cyclin A and B/ CDK1 complexes are activated in a temporal succession, the data provided here, together with these two articles, lead to the idea that cyclin A would participate in early re-replication inhibition in mammals controlled by CDK1, whereas cyclin B complexes would inhibit re-replication later.…”
Section: Discussionsupporting
confidence: 54%
“…This fits well with a crucial role of cyclin B/CDK1 complexes in this phenotype, probably together with cyclin A/CDK1 complexes. Indeed, re-replication has been reported after cyclin A ablation in drosophila, and also after cyclin A knock down together with Emi-1 in mammals (Mihaylov et al, 2002;Machida and Dutta, 2007). As cyclin A and B/ CDK1 complexes are activated in a temporal succession, the data provided here, together with these two articles, lead to the idea that cyclin A would participate in early re-replication inhibition in mammals controlled by CDK1, whereas cyclin B complexes would inhibit re-replication later.…”
Section: Discussionsupporting
confidence: 54%
“…There may be differences between the two organisms in the way checkpoint controls are exercised. It has recently been reported that cultured Drosophila cells accumulate excessive amounts of DNA (up to 8n) when geminin synthesis is inhibited by interfering RNA (Mihaylov et al, 2002). This may indicate that Drosophila cells are more dependent on a geminin-requiring mechanism to inhibit rereplication than vertebrate cells.…”
Section: Discussionmentioning
confidence: 93%
“…These control experiments show that the transfection of cells with siRNA duplexes targeting cyclin A2 at 24 h before exposure to HU does not lead to a cell cycle arrest. Lastly, depletion of cyclin A2 has been suggested to cause changes in ploidy (Mihaylov et al, 2002). However, there is no indication so far that cells with altered ploidy cannot undergo additional rounds of centriole duplication (Mantel et al, 1999;Guarguaglini et al, 2005).…”
Section: A-amanitin Inhibits Hpv-16 E7-and Hu-induced Centriole Overdmentioning
confidence: 99%